Vibrio albensis bacteremia: A case report and systematic review - Ashraf O.E. Ahmed (17545632) (2022)
Vibrio species are gram-negative rods usually known to cause gastroenteritis and infrequently extraintestinal infections in humans. V. cholerae are classically associated with cholera epidemics, particularly serogroup O1 and serogroup O139. However, Vibrio albensis, a non-O1/ non-O-139 serogroup is rarely implicated in human infections. Thus, there is a paucity of data available on the pathogenic profile of V. albensis infections in humans and more research is needed to further delineate the clinical course and management. To fill this gap in the literature, we present the successful management of V. albensis bacteremia in a 64-year-old patient, and we conducted a systematic review of V. albensis infections reported to date, aiming to explore the clinical presentation, course, and management of V. albensis infections. Other Information Published in: IDCases License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.idcr.2022.e01551